ANALISA KINERJA KEUANGAN PADA KOPERASI SIMPAN PINJAM DAN PEMBIAYAAN SYARIAH ”USAHA BAROKAH” JATIPURNO (Studi Kasus Syariah KSPPS Usaha Barokah Jatipurno - Tri Nur Setiawati; Prastiwi, Iin Emy; Indra Lila Kusuma (Jurnal Ilmiah Ekonomi Islam, 2025)
This study aims to analyze the financial performance of the cooperative by using various financial ratios as outlined in the Decree of the Minister of Cooperatives and Small and Medium Enterprises No. 35.3/Per/M.KUKM/X/2007. The analysis of financial reports is also intended to serve as a reference for the new cooperative management, as the term of the previous management has ended. Data collection techniques include documentation, observation, and interviews. Financial Performance Analysis of KSPPS Usaha Barokah Jatipurno Wonogiri (based on the Ministerial Decree No. 35.3/Per/M.KUKM/X/2007): Equity to Total Capital Ratio Score: 4.50 (2023) and 5.00 (2024) out of 5.00 Category: healthy. Indicates that the cooperative has a strong equity position compared to its total capital. Efficiency Score: 3.00 (2023 and 2024) out of 4.00 Category: moderately efficient. Reflects that the cooperative's asset utilization in serving members is adequate but still has room for improvement. Fixed Assets to Total Assets Ratio Score: 4.00 (2023 and 2024) out of 4.00 Category: good. Shows that the proportion of fixed assets to total assets is well-balanced. Liquidity Score: 7.50 (2023 and 2024) out of 10.00 Category: moderately liquid. Indicates that the cooperative is fairly capable of meeting its short-term obligations. Asset Profitability (Return on Assets) Score: 0.75 (2023 and 2024) out of 3.00 Category: low. Shows that the cooperative’s ability to generate profit from its total assets is still lacking. Equity Profitability (Return on Equity) Score: 3.00 (2022 and 2023) out of 3.00 Category: high. Demonstrates that the cooperative is highly effective in generating profit from its own capital. Despite some strong indicators, the findings highlight the need to increase equity, improve service delivery, optimize fund management, and evaluate that can’t declining performance areas.